PENGARUH LINGKUNGAN KERJA, EMPLOYEE ENGAGEMENT DAN KECERDASAN EMOSIONAL TERHADAP PERILAKU KEWARGAAN ORGANISASI PADA PETUGAS PENANGANAN PRASARANA DAN SARANA UMUM (PPSU) DI KELURAHAN KALISARI - Madelin Sarah (2023)
This quantitative research has the aim of testing and knowing "The Effect of Work Environment, Employee Engagement, and Emotional Intelligence on Organizational Citizenship Behavior at Public Infrastructure and Handling Officers (PPSU) in Kalisari". Respondents used in the study amounted to 69 respondents Public Infrastructure and Handling Officers (PPSU) in Kalisari. Data collection was carried out through distributing questionnaires and the data analysis technique used is the Partial Least Square (PLS) method. The results obtained in the test are (1) work environment has a significant effect on Organizational Citizenship Behavior (2) employee engagement has a significant effect on Organizational Citizenship Behavior (3) emotional intelligence has a significant effect on Organizational Citizenship Behavior.